Target acquired [large type] - Eason, Lynette (Eason, Lynette. Lake City heroes, 2025)
Tough-as-nails Kenzie King has finally earned her place as a tactical medic on a SWAT team. But not everyone on the all-male team accepts her. Rumour is, she didn't get the position because of what she could do but because of who she knew. Which means she has to work harder and longer than anyone else to prove herself. Cole Garrison is a man with deep faith who is finally ready to settle down and build a family of his own - if he can find the right person, that is. Kenzie sure has set off his interest meter, but trouble seems to follow in her wake. Since she joined the team, someone has begun to ambush and pick off team members, one by one. It's all hands on deck to discover the culprit and end the killing. Can Kenzie and Cole put aside their differences and work together as a team? Or will their budding attraction be snuffed out by a sniper's bullet?